Biorremediación de Bifenilos Policlorados (PCBs) por hongos de pudrición blanca nativos de la Provincia de Misiones - Sadañoski, Marcela Alejandra (2019)
The aim of this work was to evaluate the ability of Argentinean white rot fungi native from Misiones province, to remove PCBs as bioremediation strategy. Three strains: Lentinus sajor-caju LBM 105, Pycnoporus sanguineus LBM 105 and Irpex lacteus BAFC 1171 which displayed high tolerance to PCBs and produced ligninolytic enzymes in solid media were selected. The best results were obtained with L. sajor-caju LBM 105, which lead to PCBs removals of 95% and 92% in complex and N-limited synthetic liquid media respectively, after 35 days of incubation. PCBs affected fungal growth, morphology and enzymatic laccase activity of the three strains. Biostimulation treatments with sugarcane bagasse and biaugmentation with monocultures and co-cultures of L. sajor-caju LBM 105 and P. sanguineus LBM 105 were efficient for PCBs-contaminated soil remediation. Bioaugmentation treatment with the co-culture removed 91% of PCBs, followed by treatment with L. sajor-caju LBM 105 (90%). Biostimulation as well as the treatment with P. sanguineus LBM 105 removed 88% of PCBs concentration. In addition, the toxicity was reduced and the quality of the treated soil increased.